Economic corridors and regional development: The Malaysian experience - Premachandra Athukorala; Suresh Narayanan (Asian Development Bank (ADB), 2017)
This paper examines prerequisites for a successful interstate economic corridor development program in a country with a federal system of government through an in-depth study of the design, implementation, and the developmental impact of the Northern Corridor Economic Region (NCER) in Malaysia that encompasses the states of Penang, Kedah, Perak, and Perlis. The analysis suggests that the NCER has the potential to leverage on the core strengths of the state of Penang - global connectivity, mature business ecosystem with a strong presence of multinational enterprises, and sizable talent pool - in order to redress the widening interregional and urban - rural development divide. While it is too early to assess the full outcome of NCER initiative, a potential problem looms in the future. The Northern Corridor Implementing Authority (NCIA), charged with implementing projects in the NCER, is structured with no formal positions allotted to planning officials from the member states. This will not pose problems in implementing projects that are in broad alignment with the interest of the states. Conflicts will arise, however, when state and NCIA views on projects differ. This potential problem can be overcome by restructuring the NCIA to allow for the formal inclusion of planning representatives from member states.
Keywords: O18; O21; O53; 330; economic corridor; Malaysia; regional development